Availability analysis for embedded system with N-version programming using fuzzy approach. (1st January 2015) - Kaushik, Manju; Kumar, Gireesh; Preeti,; Sharma, Richa
This present study deals with the conventional as well as fuzzy availability analysis of an embedded system considering both the software and hardware reliability. In this model, we have considered a specified number of subsystems composed of software and hardware components arranged in series. In N-version programming for the execution of the same task, N-versions of software are running at same time. Further, the assumption of rebooting is also taken in to consideration. Markov analysis has been done in which all the rates are exponentially distributed. To validate the proposed model, a numerical illustration is also carried out for conventional and fuzzy approaches for analysing the system performance by assuming the triangular membership function of the system descriptors.